Role of Commercial Banks In India: The Evolution of Rural Financial Institutions in India (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In post- independence India, in order to facilitateimprovements in agricultural production and attain food self – sufficiency, thestance of policy was to ensure sufficient and timely credit at “reasonable”rates of interest to as large a segment of the rural population as possible(Rangarajan 1996). The strategy to achieve this was threefold: expansion of theinstitutional base, directed lending to disadvantage borrowers, and creditprovision at concessional rates of interest. The latter was justified in termsof the perceived  mismatch between thelonger term returns of farm investment in relation to cultivator households ‘short term consumption needs and requirements to service the loans. Fisher andSriram (2006) identify three post-independence phases in rural credit  provision . First , the 1950‘s up to the mid– 1960 ‘ s when cooperatives were the institutional vehicles of choice ;second, the 1970’ s and 1980’ s    whenattention shifted to commercial  banksand RDBs and third, the reform period in the early 1990’ s which saw there-structuring of the banking system , the emergence of SHGs and a growingnumber of MFIs , In terms of scale, spread, costs, risks, and the inter-temporal nature of credit markets, financial institutions and agents in Indiaface formidable challenges in meeting the diverse financial service needs ofthe country’s rular population. The present rular financial infrastructurecomprises a wide variety of formal, semi- formal and informal financial serviceproviders , with distinctive cultures and characteristics. The number oforganizations and agents is very substantial : 33,553 rular and semi- urbanbranches of commercial banks , 13,932 rular and semi-urban branches of ReginolRural Banks, 1.09 lakh primary cooperatives, 1,000 NGO-MFIs registered ascompanies (section 25) and nearly three million SHGs. Even more numerous arethe myriad of informal agents constituting a great range of financial serviceproviders across the country. Different segments of the financialinfrastructure have not developed uniformly or simultaneously , and theirrelative standing in terms of government policy and intervention has changedover time. Moreover, financial institutions have themselves influencedgovernment policy (Jones 2006) . In the following paragraphs , an attempt ismade to trace the forces and compulsions that have led to the development ofparticular rural financial institutions in the country, to outline the changingfortunes and shares of these different systems , to show the present gapbetween rural financial needs and provisions , and to assess policy options toreduce this gap through institutional development , linkages and reform.